DiverCIAT - Ngonidzashe Chirinda, Soils and Climate Change Scientist - International Center for Tropical Agriculture (2016)
CIAT Soils and Climate Change Scientist Ngoni Chirinda discusses growing up in Zimbabwe and how that led him to a career in international development.